Narrative review of telemedicine consultation in medical practice - Di Cerbo A; Morales-Medina JC; Palmieri B; Iannitti T (Patient Preference and Adherence, 2015)
Alessandro Di Cerbo,1,2 Julio Cesar Morales-Medina,3 Beniamino Palmieri,1,2 Tommaso Iannitti4 1Poliambulatorio del Secondo Parere, 2Department of General Surgery and Surgical Specialties, Surgical Clinic, University of Modena and Reggio Emilia Medical School, Modena, Italy; 3Centro de Investigación en Reproducción Animal, CINVESTAV, Universidad Autónoma de Tlaxcala, Tlaxcala de Xicohténcatl, Mexico; 4Department of Neuroscience, Sheffield Institute for Translational Neuroscience (SITraN), University of Sheffield, Sheffield, UK Background: The use of telemedicine has grown across several medical fields, due to the increasing number of “e-patients”.Objective: This narrative review gives an overview of the growing use of telemedicine in different medical specialties, showing how its use can improve medical care.Methods: A PubMed/Medline, Embase, Web of Science, and Scopus search was performed using the following keywords: telemedicine, teleconsultation, telehealth, e-health, and e-medicine. Selected papers from 1996 to 2014 were chosen on the basis of their content (quality and novelty).Results: Telemedicine has already been applied to different areas of medical practice, and it is as effective as face-to-face medical care, at least for the diagnosis and treatment of some pathological conditions.Conclusion: Telemedicine is time- and cost-effective for both patients and health care professionals, encouraging its use on a larger scale. Telemedicine provides specialist medical care to patients who have poor access to hospitals, and ensures continuity of care and optimal use of available health resources. The use of telemedicine opens new perspectives for patients seeking a medical second opinion for their pathology, since they can have remote access to medical resources that would otherwise require enormous costs and time. Keywords: telemedicine, health care, patient